A rapid method for determining low concentrations of 210Pb in drinking water using MnO2 fibers. (November 2022) - Aviv, O.; Vaknin, D.; Yungrais, Z.; Shonkor, S.; Haquin, G.; Datz, H.
Abstract: A rapid method for determining low activity concentrations of 210 Pb in drinking water was developed and tested. The method consists of a few stages for sample preparation that involve passing 12 L of water through a column with acrylic fibers implanted with MnO2 (used to adsorb 210 Pb). The MnO2 fibers are oven-dried, compressed and measured by a broad-energy germanium detector used to quantify 210 Pb via its characteristic 46.5 keV γ-ray. The time taken for sample preparation is approximately 4 h and recovery factors for lead in tap water of 87 ± 3% were achieved. After a measurement duration of 4 h, the minimum detectable activity concentration reaches 0.02 Bq/L for 210 Pb, being well below the respective limit for drinking water in Israel (0.2 Bq/L) as well as the value recommended by the World Health Organization (0.1 Bq/L). Furthermore, a measurement duration of 48 h provides a minimum detectable activity concentration of ∼0.006 Bq/L, which is similar in magnitude to other, well-established methods that rely on lengthy and rather complex procedures. Thus, the combination of MnO2 fibers and gamma-ray spectrometry may be attractive for routine use by analytical laboratories that monitor radioactivity in drinking water. Highlights: A new method for evaluating low concentrations of 210 Pb in drinking water was developed and tested. The overall time taken for sample preparation and measurement is typically below 12 h. The recovery factor for 210 Pb in MnO2 fibers was found to be 87%. The MDC for 210 Pb in drinking water was found to be typically ∼0.01 Bq/L.